REVISITING THE NIGERIAN CIVIL WAR: THE ROLE OF THE IBIBIO IN THE COLLAPSE OF BIAFRA, 1967-1970 - GODWIN STEPHEN EMAH; PETER FOLORUNSHO ADEBAYO (International Studies Journal)
The civil war in Nigeria (6 th July – 15th January, 1970) involved the Eastern region and the Federal government. The Ibibio (an ethnic nationality in the Eastern region) rather than fight on the side of the Eastern region (Biafra), fought on side of the Federal government. The study made use of primary and secondary sources, the primary sources included oral interview, archival materials and government publications. Relevant text books, articles in journals and unpublished thesis were secondary sources. The study revealed that the Ibibio sabotaged the efforts of the Biafrans and annihilated their dream of becoming a sovereign nation by giving supportive hands to the federal troops which aided their victory. Few Ibibio indigenes that supported Biafra were former federal military officers and some in the civil service.The study also revealed that the Ibibio supported the federal troops because they were marginalized and oppressed by the Igbo in the Eastern region. The study showed clearly that the Ibibio played significant role in collapse of Biafra through employment of several acts to sabotage the aspirations of the Biafrans. They provided information and logistics to the federal troops through reconnaissance. The Ibibio equally contributed personnel to the federal troops through organization of vigilante groups. The persistent misconception that the Ibibio fought on the side of the Biafrans has been corrected by this study.